Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Koperasi Mahasiswa Universitas Tidar - Wafa, Muhamad Jauharul; Manasikana, Arina; Wulandari, Septiana; Syarifatussuroya, Zulfa; Cahyani, Nabyla Tri; Cahyaningrum, Elsa Ayu; Nugraha, Joko Tri (FIA Unkris Press, 2025)
This research aims to assess the level of satisfaction among students at Tidar University regarding the services provided by the Student Cooperative (Kopma), which plays a crucial role in meeting students' daily needs and serves as a platform for developing entrepreneurial skills. The methodology employed in this study is quantitative, with data collection conducted through the distribution of questionnaires to a number of students from various faculties. The satisfaction assessment refers to the five dimensions of SERVQUAL, namely assurance, reliability, tangibility, empathy, and responsiveness. The analysis results indicate that, in general, students feel 'satisfied' with the services of Kopma, particularly in the aspects of assurance, reliability, tangibility, and empathy, with satisfaction levels ranging from 61% to 76%. These aspects reflect the students' trust in the cooperative's ability to provide reliable services, good physical appearance, and the professionalism and care of the staff. However, there are several indicators that received a 'fairly satisfied' rating, such as issues related to security and cleanliness in the cooperative area, the quality of the goods offered, and the speed and effectiveness in handling complaints and suggestions from students. These findings suggest that the level of student satisfaction has a positive relationship with their loyalty to the cooperative. Students who feel satisfied are more likely to return to use the services and recommend them to their peers. Therefore, the cooperative management needs to conduct regular evaluations and continuously improve service quality to create a better experience, enhance customer loyalty, and support the sustainability and development of the student cooperative within the Tidar University environment.